Multi-Band Surgery for Repaired Tetralogy of Fallot Patients With Reduced Right Ventricle Ejection Fraction: A Pilot Study - Yu, Han; del Nido, Pedro J.; Geva, Tal; Yang, Chun; Wu, Zheyang; Rathod, Rahul H.; Huang, Xueying; Billiar, Kristen L.; Tang, Dalin (Frontiers in Physiology, 2020)
Introduction: Right ventricle failure is one of the most common symptoms among patients with repaired tetralogy of Fallot. Current surgery treatment approach including pulmonary valve replacement (PVR) showed mixed post-surgery outcomes. A novel PVR surgical strategy using active contracting bands is proposed to improve post-PVR outcome. In lieu of testing the risky surgical procedures on real patients, computational simulations (virtual surgery) using biomechanical ventricle models based on patient-specific cardiac magnetic resonance (CMR) data were performed to test the feasibility of the PVR procedures with active contracting bands. Different band combination and insertion options were tested to identify optimal surgery designs. Method: CMR data were obtained from one TOF patient (male, age: 23) with informed consent obtained. A total of 21 finite element models were constructed and solved following our established procedures to investigate the outcomes of band insertion surgery. The nonlinear anisotropic Mooney-Rivlin model was used as the material model. Five different band insertion plans were simulated (3 single band models with different band locations; 1 model with 2 bands, and 1 model with 3 bands). Three band contraction ratios (10%, 15% and 20%) and passive bands (0% contraction ratio) were tested. Right ventricle (RV) ejection fraction was used as the measure for cardiac function. Results: RV ejection fraction from the 3-band model with 20% contraction increased to 41.58% from baseline 37.38%, a 4.20% absolute improvement. RV ejection fraction from the other 4 band models with 20% contraction rate were 39.70%, 39.45%, 40.70% (2-band), and 39.17%, respectively. Mean RV stress and strain values from all 21 models showed only modest differences (5-11%). Discussion and Conclusion: This pilot feasibility modeling study demonstrated the possibility that the use of active contracting bands in PVR surgery could improve RV cardiac function for patients with repaired TOF. The modeling results and surgical strategy need to be further developed and validated by multi-patient study and animal experiments before clinical trial could become possible. Tissue regeneration techniques are need to produce materials for the contracting bands.